GameSphere BD - Voucher Selling Application - REZA, MD RASHEDUJJAMAN; Mohd Zainuri Saringat (Applied Information Technology And Computer Science, 2025)
The exponential expansion of online gaming has highlited major issues in gaming e-commerce, particularly in game transactions and the lake of user-centric features. The GameSphere BD program created an eye catching e-commerce software for gamers that priorizes security, usability, and trust to address these concerns. The study uses an iterative development methodology, through testing, and validation to create a safe platform that lets gamers buy game vouchers with confidence using intutive interfaces and fortified payment gateways. Improved user interface, safe transactions, and loyalty programs boost user confidence, according o key results. The discussion emphasizes this platform’s potential to revolotionize gaming e-commerce and suggest future improvements.